2001
DOI: 10.1200/jco.2001.19.23.4314
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Blood and Marrow Transplantation for Hodgkin’s Lymphoma

Abstract: There seems to be a clinical graft-versus-HL effect associated with allo BMT. Allo BMT for HL also seems to have a lower risk of secondary AML/MDS than auto BMT. Thus, allo BMT warrants continued study in HL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
110
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 23 publications
7
110
0
Order By: Relevance
“…It was demonstrated that the disadvantage of male sex, which was a known adverse prognostic factor in HL at diagnosis [19], persisted even after the performance of allogeneic HSCT. Some studies have suggested the existence of a graft-versusHodgkin lymphoma effect [18,20,21]. In our study, the presence of acute or chronic GVHD did not affect PFS and RR.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…It was demonstrated that the disadvantage of male sex, which was a known adverse prognostic factor in HL at diagnosis [19], persisted even after the performance of allogeneic HSCT. Some studies have suggested the existence of a graft-versusHodgkin lymphoma effect [18,20,21]. In our study, the presence of acute or chronic GVHD did not affect PFS and RR.…”
Section: Discussionsupporting
confidence: 45%
“…Akpek et al compared autologous HSCT and allogeneic HSCT from an HLA-matched sibling for patients with relapsed and refractory HL who had not received HSCT previously [20]. They demonstrated that there were no significant differences in OS and RR.…”
Section: Discussionmentioning
confidence: 99%
“…Transplant results have improved over time, probably due to improvements in supportive care and refinements in patient selection. 10,16,27 Thus, the lack of difference further supports the conclusion that eBEAM does not seem to improve results. We did find better EFS and OS with eBEAM over sBEAM in HD patients, although the difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 68%
“…64 While MDS/sAML is a significant concern in heavily pretreated high-risk relapsed/ refractory lymphoma patients treated with high-dose therapy and AutoSCT, MDS/sAML is a rare complication after AlloSCT. 65 …”
Section: Sct For Childhood Hdmentioning
confidence: 99%